INITIAL SANITARY HYGIENIC SKILLS EDUCATION IN INFANTS - S.M. Sharkov ("Paediatrician" Publishers LLC, 2010)
It is universally recognized that toilet training must be started in children 18-36 months old. It is recommended to hold child- oriented Brazelton's method. This approach is most physiological and more effective that toilet education at the first year of life, based on reflex.Key words: children, age, toilet training.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):174-178)